INFLUENCE ANALYSIS EASY USE AND ONLINE SHOPPING EXPERIENCE ON CONSUMER SATISFACTION AND ITS IMPACT ON RETURN INTENTION (STUDY OF E-MARKETPLACE USERS IN SEMARANG CITY) - Farhandhia Devangga; I Made Bayu Dirgantara (Lafadz Jaya Publisher, 2023)
The e-commerce platform is a sector that continues to grow rapidly where customer satisfaction is a very important factor for the target marketplace service provider who hopes that when consumers feel satisfied, they will make repeat purchases. The condition for achieving quality in this sector is continuous development in the area of customer solutions. The uniqueness of the electronic communications sector lies in the fact that the system of convenience provided is the main factor that distinguishes a company from its competitors. This study aims to analyze the factors that can increase the repurchase intention of e-Marketplace users in Semarang City. The sample of this study amounted to 150 respondents who were willing to answer the questions given by the researcher. Determination of the sample using nonprobability sampling technique with purposive sampling method, namely the researcher determines the criteria to become respondents (Sugiyono, 2016). The technique of distributing questionnaires uses accidental sampling. The determination of the sample based on an accidental meeting can then be used as a sample with the sample criteria that have been determined above (Mas'ud, 2014). The tool used to analyze the data is AMOS 22.00 with SEM (Structural Equation Modeling) method. The results of the study show that the five hypotheses proposed can be accepted as a whole. There is a significant effect of ease of use on consumer satisfaction with a p-value of 0.035. There is a significant effect of ease of use on repurchase intention with a p-value of 0.018. There is a significant effect of shopping experience on consumer satisfaction with a p-value of 0.008. There is a significant effect of shopping experience on repurchase intention with a p-value of which means less than zero <0.05. There is a significant effect of consumer satisfaction on repurchase intention with a p-value of 0.023.